Corona discharge and arcing around wires under the influence of high electric fields - Evans, John Lee (2018)
An Electromagnetic Pulse (EMP) resulting from, for example, the detonation of a nuclear weapon is characterised by a wave of electromagnetic activity able to couple with power lines and electro-sensitive equipment with the potential of rendering an establishment or on a greater scale, a whole city impotent. Protection against such occurrences is of paramount importance. It is now accepted that an important consideration when devising protective schemes against such phenomena is an accurate understanding of the effects on propagating waveforms such as those coupled to wires, when electrical breakdown of the dielectric material surrounding such wires occurs, otherwise known as electrical discharge. Such issues can occur around the affected wires if the electric fields generated exceed the dielectric strength of the surrounding medium, typically air or soil. Under these circumstances, the signature of the coupled waveform is known to change in characteristic ways. The form and degree of distortion needs to be understood if the harmful effects are to be prevented by protection systems put in place. The purpose of this thesis is to first describe the mechanisms that lead to the development of the Nuclear–Electromagnetic Pulse (NEMP) and the mechanisms of the discharge that can result once such pulses have coupled to a wire. Next, some of the previous corona-modelling approaches are discussed. Many of the modelling approaches have been applied to 1-D transmission-line simulations. When 3-D simulations have been performed, the Finite-Difference (Time Domain) or FD-TD approach seems to be the preferred method. At the time of writing, no 3-D Transmission Line simulations of discharge phenomena around wires were available. Hence, here, the 3-D Transmission Line Modelling Method (TLM) is described with a view to modelling such behaviour. In particular, the Embedded-Wire-Node (EWN) is used to model the discharge development around the wire. This is a fine-wire technique used to reduce computational fatigue. The node can be adapted to accept changes related to electrical discharge allowing for a real-time, self-consistent recreation of such effects. The 3-D TLM approach proves to be a decent candidate to the modelling of such behaviour. Both advantages and disadvantages of this method are discussed.